Platelet yield and recovery following the PRGF-U1 protocol in a Peruvian population - Augusto Aguirre-Aguilar; Heber Arbildo-Vega; Antonio Aguirre-Aguilar (Universidad de Concepción., 2018)
Objective: To determine the platelet recovery and yield of the PRGF-U1 protocol in a Peruvian population. Methods: An observational, descriptive and cross-sectional study was conducted with a simple random probability sample of 32 patients who attended the Laboratorio Scalab in Trujillo, Peru. A blood sample was taken from each patient in order to obtain the concentration of platelets and before and after the PRGF-U1 protocol, in order to determine platelet recovery and yield. To compare basal platelet concentrations and platelet recovery and yield with gender and age, the chisquare test, Student's t-distribution and Pearson's correlation coefficient were used considering a significance level of p<0.05. Results: Platelet yield was less than 2.2 in two patients and greater than or equal to 2.2 in 30 patients; platelet recovery was equal to 0.4 in 30 patients and greater than 0.4 in two patients. A statistically significant relationship (p<0.05) between basal platelet count and age was found when comparing basal platelet count, platelet recovery and platelet yield according to gender and age, but no significant relationship between the other variables (p>0.05). Conclusion: The PRGF-U1 protocol presents optimal platelet yield and minimal expected platelet recovery.